I-PD controller for integrating plus time-delay Processes - Chakraborty S.; Ghosh S.; Naskar A.K. (My University, 2025)
An integral-proportional derivative (I-PD) control strategy for integrating plus time-delay processes is proposed. The proposed scheme consists of an inner PD loop and an outer I-loop for taking care of the servo as well as the regulatory action. Explicit formulas for tuning of the proposed controller are derived in terms of gain margin, phase margin and critical gain. Moreover, pole-placement and frequency loop-shaping design methods are also explored for designing the I-PD controller. Simulation results show the superiority of the proposed I-PD controller over conventional P/PI/PID ones for integrating processes. The design is also validated through experiments on a temperature control process. © The Institution of Engineering and Technology 2017.